2023
DOI: 10.1158/1940-6207.capr-22-0314
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Lung Cancer Screening in a Minnesota Urban Indigenous Community: A Community-Based, Participatory, Action-Oriented Study

Abstract: Although lung cancer screening with annual low-dose chest computed tomography has been shown to reduce lung cancer deaths, it remains underutilized. Northern Plains American Indian and Alaska Native communities experience extreme lung cancer disparities, and little is known about the acceptance and adoption of lung cancer screening in these groups. We conducted interviews with healthcare professionals and focus groups with patients in an urban Minnesota community clinic serving AI/AN. Data collection took plac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There are few studies specific to LCS for AI/AN people, but our results confirm and extend the findings that there are both limitations in knowledge in this population and several barriers to LCS ( Welch et al, 2024 , Anderson et al, 2023 ). Welch et al, also highlighted the impact of multigenerational smoking behavior among native elders, a theme that arose in the present study ( Welch et al, 2024 ), and Anderson, et al, also identified interest in culturally-tailored programming delivered in a community setting among a small sample of LCS-eligible or near-eligible urban AI/AN participants from Minnesota ( Anderson et al, 2023 ). Studies have similarly found negative attitudes held towards some smoking cessation modalities, which could be a barrier to providing LCS and discussing commercial tobacco cessation ( Burgess et al, 2007 , Gryczynski et al, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
“…There are few studies specific to LCS for AI/AN people, but our results confirm and extend the findings that there are both limitations in knowledge in this population and several barriers to LCS ( Welch et al, 2024 , Anderson et al, 2023 ). Welch et al, also highlighted the impact of multigenerational smoking behavior among native elders, a theme that arose in the present study ( Welch et al, 2024 ), and Anderson, et al, also identified interest in culturally-tailored programming delivered in a community setting among a small sample of LCS-eligible or near-eligible urban AI/AN participants from Minnesota ( Anderson et al, 2023 ). Studies have similarly found negative attitudes held towards some smoking cessation modalities, which could be a barrier to providing LCS and discussing commercial tobacco cessation ( Burgess et al, 2007 , Gryczynski et al, 2010 ).…”
Section: Discussionsupporting
confidence: 88%
“…Although people who smoke in the US population at large experience perceived and internalized stigma around cigarette smoking, we believe older Indigenous Minnesotans do not perceive such stigma. The cultural practices and beliefs stemming from colonization and commercialization of a sacred medicine (tobacco), may have insulated 11 against wider stigmatizing messages associated with public messaging to promote tobacco control. Looking at tobacco use within the context of colonization and commercialization of a sacred medicine, these findings represent a unique opportunity to end the misperception that AI/AN who choose to use commercial tobacco do not care about their health.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, patients of this clinic reported barriers to LCS including a mistrust of health systems in general (but a strong trust in their clinic), diagnosis knowledge avoidance, low-perceived personal value for a diagnosis yet a high-perceived community value for wellbeing, and practical resource barriers such as transportation. 11 This information guided the process of making and testing a culturally targeted brochure, used within this study. Culturally targeted approaches to LCS, such as the intervention described within this study, are needed to ensure that contextually appropriate care is provided to historically oppressed communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging the community as equal partners fosters mutual learning, builds trust, and ensures that interventions are grounded in the community's needs, values, and cultural contexts. This approach promotes community ownership and the sustainability of interventions [170][171][172][173]. Cultural competence in health education involves understanding and respecting cultural beliefs, practices, and communication styles.…”
Section: Community Engagement and Health Educationmentioning
confidence: 99%